Implementation of Continuous-Assessment on Postgraduate Program - Wasis Wasis; Titin Sunarti; Mukhayyarotin Niswati Rodliyatul Jauhariyah (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The assessment approach is crucial to achieving learning outcomes. Contonuous-Assessment (CA) is one alternative assessment that can be used to increase various skills. This preliminary study aims to: (1) formulate CA and project-based assessment in higher education; (2) describe the lecturer's and students' perception of CA in the postgraduate program; (3) map course assignments within the framework of CA at the postgraduate level. Method: Data was collected through Forum Group Discussions (FGDs) and questionnaires. Data were analyzed both qualitatively and quantitatively. Results: The results show that the conceptual study of the CA should pay attention to the purposes, improve the learning process, involve students fully and purposefully in their learning, and explore the factors that influence the learning process. The design of CA is realized as demand mapping for each course in the form of products or small projects as part of the stages for completing a thesis/dissertation. Most lecturers and students agree that the lecture process uses a CA design in which each course contributes to achieving the thesis/dissertation. A small number of them disagree and give some suggestions. Novelty: The novelty of this research is to produce a mapping of assignments from all courses, which leads to the completion of writing a thesis/dissertation.